MINAT BELAJAR SISWA PADA PELAJARAN PENJAS ORKES TERHADAP HASIL BELAJAR PELAJARAN PENJAS ORKES SISWA SMA NEGERI Se-Kecamatan Pengandonan - Farizal Imansyah (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
Abstract— The purpose of this research are: 1) To know whether or not there is interest of student learning on the subject of orchestra on the learning result of orchestra of the students of SMA Negeri in the district of Pengandonan, and 2) to know what percentage of student's interest in the orchestra examination lesson. The population of this study is all students of High School in the District, amounting to 2589 students. Research sample 10% from population that is 344 student with sample proportional random sampling technique. collection of questionnaire method, documentation and interview. Analysis techniques used descriptive analysis and regression analysis.The population of this study is all students of state Senior High School in the District of 2589 students. Research sample 10% from population that is 344 student with sample proportional random sampling technique. Data collection of questionnaire method, documentation and interview. Data analysis techniques used descriptive analysis and regression analysis.The result of the study of the students' learning interest in the High School Orchestra lecture (76.12%) and the learning result of the orchestra has been good with an average of 7.00. Regression analysis results obtained regression equation = 2.997 + 0.023X. Test of significance with F test obtained Fhitung = 219,118> Ftable = 3,87. the regression equation is significant so that it is expressed There is influence of student's learning interest in the lesson of orchestra of learning result of student orchestra examination 39,1%.Based on the results of the study, the authors provide suggestions: 1) To obtain high learning outcomes students need to grow their interest in the orchestra lesson especially the perseverance in learning the orchestra in earnest, 2) For other researchers who want to conduct similar research can make as reference material and can take other factors such as the physical condition of students. Keywords— Character education, literary learning, local wisdom Abstrak— Tujuan penelitian ini adalah : 1) Untuk mengetahui ada tidaknya minat belajar siswa pada pelajaran Penjas Orkes terhadap hasil belajar Penjas Orkes siswa SMA Negeri se-kecamatan Pengandonan, dan 2) Untuk mengetahui berapa persen minat belajar siswa pada pelajaran Penjas Orkes. Populasi penelitian ini seluruh siswa SMA Negeri se-Kecamatan yang berjumlah 2589 siswa. Sampel penelitian 10% dari populasi yaitu 344 siswa dengan teknik pengambilan sampel proposional random sampling. Pengumpulan data metode angket, dokumentasi dan wawancara. Teknik analisis data menggunakan analisis deskriptif dan analisis regresi. Hasil penelitian minat belajar siswa pelajaran Penjas Orkes tinggi (76,12%) dan hasil belajar Penjas Orkes telah baik dengan rata-rata 7,00. Hasil analisis regresi diperoleh persamaan regresi = 2,997 + 0,023X. Uji keberartian dengan uji F diperoleh Fhitung = 219,118 > Ftabel = 3,87. persamaan regresi signifikan sehingga dinyatakan Ada pengaruh minat belajar siswa pada pelajaran Penjas Orkes terhadap hasil belajar Penjas Orkes siswa sebesar 39,1%.Berdasarkan hasil penelitian,penulis memberikan saran: 1) Untuk mendapatkan hasil belajar yang tinggi siswa perlu menumbuhkan minatnya pada pelajaran Penjas Orkes terutama ketekunannya dalam belajar Penjas Orkes dengan sungguh-sungguh, 2) Bagi peneliti lain yang hendak mengadakan penelitian sejenis dapat menjadikan sebagai bahan referensi serta dapat mengambil faktor-faktor lain seperti kondisi fisik siswa. Kata kunci— Minat Belajar dan Hasil Belajar Pelajaran Penjas Orkes